Citrus Production Under Screen as a Strategy to Protect Grapefruit Trees From Huanglongbing Disease - Ferrarezi, Rhuanito S.; Qureshi, Jawwad A.; Wright, Alan L.; Ritenour, Mark A.; Macan, Natalia P. F. (Frontiers in Plant Science, 2019)
Citrus production under enclosed structures can exclude the Asian Citrus Psyllid (ACP) and eliminate the negative effects of citrus greening or huanglongbing (HLB) disease caused by Candidatus Liberibacter asiaticus (CLas) to the grapefruit (Citrus paradisi) fresh fruit industry. Physically impeding the insect vector from accessing trees is a logical method to have disease-free groves. Our objectives were to assess the ability of enclosed screenhouses to exclude the ACP, stop HLB inoculation and dissemination, and improve fruit yield of in-ground and container-grown 6-year-old ‘Ray Ruby’ grapefruit at super-high planting densities relative to open-air trees. We built a large structure to allow commercial-scale trials and tested two production systems (screenhouse and open-air), two planting systems (in-ground and potted), and two rootstocks (‘Sour Orange’ and ‘US-897’). Four passively ventilated 1,080-m2 completely enclosed screenhouses were constructed using a 50-mesh monofilament high-density polyethylene screen. The main support for each enclosed, covered structure consisted of pressure-treated, wooden utility poles. Trees were planted in Sept/2013 on a density of 1,957 trees/ha. Irrigation was performed on-demand using two 7.6-LPH drip emitters per tree, and fertigation was applied three times/week using 15N-2.6P-22.4K water-soluble fertilizer at 180 kg N/ha. Psyllids were monitored using sticky cards and detected inside the screenhouses post a Hurricane and a tropical storm. Only trees cultivated in open-air tested positive for CLas after 6 years. There was fast disease progression for all outside treatments, with 100% infection by May/2019. Covered, in-ground trees exhibited the highest trunk diameter and canopy volume (P<0.0001). Trees grown inside screenhouses exhibited higher fruit yield than outside trees, with the highest yield observed for in-ground trees on ‘US-897’ (51,081 kg/ha) (P<0.0001). Several open-air treatments, particularly in containers, did not produce any fruit. On the other hand, potted grapefruit trees cultivated inside the enclosures had the highest soluble solids content (P<0.001). The screenhouses provided disease exclusion, increased fruit yield, and fruit quality, representing an alternative for growers interested in producing high-quality fruit for the fresh market. Production cost and economic viability still need to be evaluated for large-scale implementation.